Hemostasis and obliteration of mandibular arteriovenous malformation through direct hydroxyapatite cement injection into the molar cavity. (14th May 2010) - Gluncic, Vicko; Reid, Russell R; Baroody, Fuad M; Gottlieb, Lawrence J; Ansari, Sameer A
Abstract : A mandibular arteriovenous malformation (AVM) presented with massive molar socket bleeding and was emergently treated by tooth extraction and partial resection of the surrounding alveolar bone. To achieve hemostasis, the resultant cavity was filled with hydroxyapatite bone cement. Not only was hemostasis and alveolar reconstruction achieved, but follow-up angiography demonstrated venous outlet occlusion and retrograde AVM thrombosis requiring no further treatment.